2019
DOI: 10.1071/an16332
|View full text |Cite
|
Sign up to set email alerts
|

Adding a bio-response modifier and zinc oxide to piglet weaner diets influences immunological responses to weaning

Abstract: The effect of zinc oxide (ZnO) and a Mycobacterium smegmatis-derived bio-response modifier (BRM) supplementation on blood neutrophil functions, high-mobility group box 1 (HMGB1) protein and pro-inflammatory cytokine responses was studied in early weanling piglets. In total, 45 piglets were placed in the following five groups: basal diet only (I), supplemented with ZnO (II), supplemented with BRM (III), supplemented with ZnO plus BRM (IV) in basal diet and basal diet without weaning from dam (V). The phagocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The first line of immune system cellular defense is formed by neutrophils [ 18 , 32 ]. However, excessive neutrophil activation leads to the production of toxic mediators including MPO, which encourages tissue damage and inflammatory reactions [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first line of immune system cellular defense is formed by neutrophils [ 18 , 32 ]. However, excessive neutrophil activation leads to the production of toxic mediators including MPO, which encourages tissue damage and inflammatory reactions [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with BP and ZO supplementations, the jejunum's inflammatory damage could be mitigated to a certain extent. Another study also demonstrated that a pharmacological dose of ZnO has potent anti-inflammatory, antioxidant, and protective effects by inhibiting polymorphonuclear leukocyte population activity, as well as by quantitatively reducing MPO and MDA [ 14 , 18 ], and pro-inflammatory mediators like TNF-α and IL-1β, all of which are crucial in oxidative stress [ 37 ]. Moreover, in the current study, it was found that bacteriophage and ZnO reduced COX-2 release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During weaning, high levels of intestinal coliform bacteria commonly lead to postweaning diarrhea in pigs [43]. During colonization of the epithelial cells of the intestine by Escherichia coli, it produces enterotoxins and leads to intestinal in ammation that increases gut permeability, thus leading to diarrhea [44][45][46][47]. Therefore, ameliorating the colonization of coliform bacteria in the intestine and/or alleviating intestinal in ammation are ways to control the diarrhea condition and subsequently improving nutrient digestibility, feed e ciency, and/or growth performance.…”
Section: Discussionmentioning
confidence: 99%